Do clinical outcomes differ for day-5 versus day-6 single embryo transfers controlled for endometrial factor?. Issue 3 (March 2022) - Stankewicz, Tiffany; Ruiz-Alonso, Maria; Soler-Ibañez, Marc; Simón, Carlos; Valbuena, Diana
Abstract: Research question: Is there is a difference in clinical outcomes between day-5 versus day-6 blastocysts when transferred in a personalized embryo transfer (PET) cycle guided by Endometrial Receptivity Analysis (ERA)? Design: Multicentre, retrospective study; 260 patients who underwent a single embryo transfer with either a day-5 or day-6 blastocyst in a PET cycle guided by ERA between January 2017 and December 2019. Results: A total of 260 blastocysts were transferred in a single embryo PET cycle guided by ERA. Of those, 183 (70.4%) were day-5 blastocysts and 77 (29.6%) were day-6 blastocysts. Clinical outcomes were similar when transferring day-5 blastocysts versus day-6 blastocysts: pregnancy rate was 75.4% (138/183) and 70.1% (54/77) ( P = 0.465); implantation rate was 67.8% (124/183) and 63.6% (49/77) ( P = 0.476); and ongoing pregnancy rate was 57.9% (106/183) and 58.4% (45/77) ( P = 0.728), respectively. Conclusions: The data suggest that the clinical potential of day-5 and day-6 blastocysts are similar, as no difference in clinical outcomes are observed when transferring at the time of optimal endometrial receptivity as determined by ERA.